Remarks at the U.S. Global Leadership Coalition Annual Conference, Washington, D.C., June 25, 2013 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, talks about the goal to get the rates of poverty down below three percent by 2030. Economic growth is critical, especially in the private sector, in developing countries. He expresses the need for private sector investment and to do this in close cooperation with the Official Development Assistance that’s going into these countries. He discusses battling climate change, and the need for social movements in developing countries to make it happen. He then fielded questions on business myopia, results-oriented approach, corruption, and education.